Analysis of the Effectiveness of Employee Performance of the Village-Owned Enterprise Mitra Bersama in Parilangke Village, Bumiraya District, Morowali Regency - Yusnita; Haris Abdul Kadir; Rahmiwati Habibu (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the effectiveness of employee performance at the Mitra Bersama Village-Owned Enterprise (BUMDes) in Parilangke Village, Bumiraya District, Morowali Regency. The method used is a descriptive qualitative approach. The results of the study indicate that the effectiveness of employee performance at the Mitra Bersama BUMDes is not optimal. This is indicated by low work discipline, limited employee competency, an unclear incentive system, and business management that has not been running optimally. Factors that influence performance effectiveness include internal factors such as employee motivation and ability, as well as external factors such as leadership, work facilities, and village government support. This study concludes that efforts are needed to improve the quality of human resources through training, improving management systems, increasing work discipline, and providing clear motivation and incentives to improve employee performance effectiveness and the success of BUMDes management.